Comparative Study of Classification Methods using Algorithms of Data Mining for Possibilities of Heart Diseases - Trikha, Bindu; Dixit, Dhruv (International Journal of Computer Sciences and Engineering, 2019)
Rate of heart-related diseases are growing day by day on a greater pace from the last 15 years, which is a major concern. Through the classification, we can understand the possibilities of such worst-case scenarios at an earlier stage which can help us in being cautious and moreover being prepared for it in the immediate future.